Was für ein Zufall!? Einige Bemerkungen über einen wenig beachteten Kern der Stochastik (mathematica didactica, 2005)
Zufall – this German word describes by no doubt part of the heart of stochastics – avery ambiguous word, shimmering between coincidence, accident, chance, hazard, random,… Here, we consider verbal traces in the context of this idea, we follow historical tracks, we discuss phenomenological views, and finally, we explore to what extent random numbers generated for some simulation by a computer algorithm are a contradiction par excellence.